Development of Cement-Coir Carbon Fiber Composites with Damage Self Detection Capability - Ismail Budiman; Subyakto Subyakto; Akhiruddin Maddu; Gustan Pari (Wood Research Journal, 2012)
Research on the manufacture of cement-carbon composite materials using carbon fiber from coconut coir fiber has been performed. Carbonization was carried out at two phases. First, it was carbonized at a temperature of 400°C for 300 min and continued by the second phase at a temperature of 800°C for 60 min. The structures of carbon fiber was measured using X-Ray Diffraction (XRD) while the sample surface analysis was carried out using Scanning Electron Microscope (SEM) and the electrical conductivity of samples was measured using LCR (Inductance Capasitance and Resistance) meter. Three carbon types (carbon without treatment, carbon soaked in 10% and 20% solution of potassium hydroxide (KOH)) were used to manufacture cement-carbon composites. Three levels of carbon content of 0.5, 0.75 and 1.0% by weight of cement were used. Results showed that the cement-carbon composite added with soaked carbon in 20% solution of KOH at 1.0% carbon content has the best properties of compressive strength (24.94 ± 1.24 MPa), modulus of rupture (MOR) (5.23 ± 0.47 MPa) and damage self-detection (load at the first crack = 21.04 N).